2017
DOI: 10.3390/ijerph14111413
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Toxoplasmosis among Clinical Laboratory Professionals: A Cross-Sectional Study in Durango, Mexico

Abstract: Background: The aim of this study was to determine the level of knowledge and practices about toxoplasmosis in a sample of clinical laboratory professionals in Mexico. Methods: 192 clinical laboratory professionals were surveyed. They were asked about (1) Toxoplasma gondii; (2) clinical manifestations, diagnosis, treatment, and epidemiology of toxoplasmosis; and (3) their practices with respect to toxoplasmosis. Results: The range of animals infected by T. gondii was known by 44.8% of participants. Clinical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 30 publications
(44 reference statements)
4
17
0
4
Order By: Relevance
“…In the current study, most of the HPs correctly answered questions related to knowledge of the infectious agent (over 80%) and the definitive hosts (64.58%). These results are consistent with those of a study conducted in Mexico, where most participants correctly answered that T. gondii is a parasite (89.6%) and that cats are definitive hosts (83.8%) [13].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, most of the HPs correctly answered questions related to knowledge of the infectious agent (over 80%) and the definitive hosts (64.58%). These results are consistent with those of a study conducted in Mexico, where most participants correctly answered that T. gondii is a parasite (89.6%) and that cats are definitive hosts (83.8%) [13].…”
Section: Discussionsupporting
confidence: 91%
“…According to the knowledge of the diagnosis, the vast majority (over 70%) of HPs knew about the detection of anti-T. gondii IgG and IgM antibodies as the pathway test for the diagnosis of toxoplasmosis, while 82 (85.42%) did not know about the avidity test as a complementary technique used in serology as a dating test for infection during the first months of pregnancy. Similarly, the lack of knowledge of the avidity test found in the present study has also been reported by physicians caring for pregnant women in Mexico and the USA, where 90.1% and 87.3% of HPs, respectively, did not know about the avidity test [13,22]. Indeed, IgM detection was not always considered a sufficient argument to conclude recent infection [23].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations